Adat in the Office: The Creative Afterlife of a New Order Cultural Policy. Issue 2 (15th March 2017) - Pollock, Ian
Abstract : This paper explores the emergence of a new genre of garments in Eastern Indonesia: 'traditional' uniforms, made from locally hand-woven cloth, which are worn twice weekly by government employees in Kupang, the capital of the province of East Nusa Tenggara (Nusa Tenggara Timur, or NTT). These uniforms, which appeared following a 1997 regulation, supported the emergence of a new, urban textile culture, and a partial decoupling of traditional clothing from adat, Indonesian customary law, even as they allowed adat to make inroads into government offices. National policy, the agitation of local elites and the innovation and conservatism of artists and ritual practitioners, all contributed to this new form of artistic and cultural expression. While attention has been paid to the domesticating power of the state on local forms of cultural expression, this example shows how attempts at control can also push cultural expressions in unexpected directions.